Cannabis sativa – A matter of physical, mental, and social health - Martins Cortez, Celia; Cortez-Calderini, Anderson; Silva, Dilson (Eastern Journal of Medical Sciences, 2022)
Several studies show that chronic marijuana use opens doors to several disorders, especially neuropsychiatric disorders. Others consider cannabinoids to be promising in therapeutic practice. Here, we present a literature review, based on selected publications on the Medline and Scielo databases, on health and cannabis use. This review aims to assist health professionals and students in understanding the growing number of marijuana users who look for help in outpatient clinics and offices. Therefore, there is an increase in the frequency of hospital admissions for psychotic disorders in clinics and specific treatment institutions. Research over the past 35 years has shown that marijuana use promotes only momentary anxiolysis. This drug alone or in combination with cigarette, when consumed for a long term, can deteriorate the user’s intellectual capacity, academic performance, and professional achievements and finally results in social isolation. The current situation demonstrates that cannabis usage is a public health issue that needs to be addressed in health policy because the majority of users get sick and lose their ability to work.